Handbook of college science teaching - Mintzes, Joel J.; Leonard, William H., 1941- (NSTA Press, 2006)
Are you still using 20th century techniques to teach science to 21st century students? Update your practices as you learn about current theory and research with the authoritative new Handbook of College Science Teaching. The Handbook offers models of teaching and learning that go beyond the typical lecture-laboratory format and provide rationales for new practices in the college classroom. It is a definitive guide for science professors in all content areas and even includes special help for those who teach nonscience majors at the freshman and sophomore levels.